Ethical Issues and Implications of Citation Practices: A Case Study on Excessive Citations, Self-Citation and Co-Author Citations - Willie, Michael Mncedisi (Manunggal Halim Jaya, 2025)
Citation practices are crucial for maintaining academic integrity, as they credit original ideas and integrate new research into the established knowledge framework. However, these practices can compromise scholarly work and misrepresent the impact of research when manipulated. This study investigates ethical concerns associated with excessive self-citation and co-author citations, examining their implications for academic integrity and citation metrics. Through a case study of a published paper—selected for its high frequency of co-author citations from accredited, peer-reviewed journals listed on Google Scholar—this research analyses citation patterns and their potential to inflate perceived scholarly impact. The findings reveal that excessive self-citation and repeated co-author citations can distort academic evaluations and create an imbalanced scholarly landscape. Supported by the literature, the study highlights the need for clear guidelines, transparency in citation practices, and vigilant monitoring by peer reviewers and editors. To preserve the integrity of academic research and ensure fair assessment, the paper recommends developing robust guidelines for citation practices and promoting transparency in citation choices.